Analyzing Shallow and Deep CNNs with Gold Standard and Random EEG Segment Selections for Coma Prognosis - Oliveira, Gustavo B. S.; Souza, Paulo D. S.; Silva, Tiago S.; Filho, João B. D.; Carneiro, Murillo G. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais do XXV Simpósio Brasileiro de Computação Aplicada à Saúde, 2025)
This study focuses on deep learning models for predicting coma outcomes using electroencephalogram (EEG) data, exploring convolutional neural networks (CNNs), particularly Shallow and Deep ConvNets, based on Filter Bank Common Spatial Patterns. A dataset of 121 EEG samples (42 favorable, 79 unfavorable) was analyzed. EEG segments were selected using two strategies and frequencies. Models were trained with 10-fold cross-validation and FTSurrogate for class balance. Shallow ConvNet showed stable performance across frequencies, while Deep ConvNet excelled at 200Hz. Simple segment selection and sampling frequency methods improved CNN performance. The findings offer insights for future research and potential clinical applications.